CREATION OF ECOLOGISTIC ENTERPRISES OF THE FOOD AND PROCESSING INDUSTRY IN WESTERN UKRAINE - STRUTYNSKA, LESYA (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The expediency, need and stages of the development of environmental science as a type of innovative activity, the purpose of which is to preserve the environment and environmental ecology, are analyzed. As an example, the effectiveness of the step-by-step introduction of ecological activities is illustrated at the processing and food industry enterprises of Western Ukraine. It has been proven that the formation of effective ecological activities cannot be done without the proper assistance of local self-government bodies and state authorities. It has been proven that with the thoughtful guidance and assistance of local self-government bodies, the processing of organic waste can be economically beneficial both for producers of food and processing industries, and for residents of local communities.The following are proposed as the main stages of implementation of effective ecological activities on the territory of local communities:- construction of regional power plants and energy installations for the production of electricity by burning biogas;- purchase and efficient operation of equipment for processing organic waste into biogas;- establishment of operational collection, sorting and processing of industrial waste;- strict control over the inadmissibility of violations by producers of sanitary and hygienic norms and requirements for waste water and waste disposal.It was noted that for the effective integration of ecology into the economy of the state through the creation of ecological enterprises, the legislative implementation of an effective environmental strategy is necessary, which will be the main competitive advantage of the enterprise in modern business conditions.
Keywords: logistics; enterprise; waste; food industry; biogas; energy; ecology; stages of formation